The Effect of the Qur'anic Interpretation Method on Students' Understanding of the Concept of Ethics in High Schools in West Java: A Case Study on Islamic Religious Education Subjects - Rohmah, Siti (Westscience Press, 2024)
This qualitative research study investigates the influence of the Qur'anic interpretation method on high school students' comprehension of ethics in West Java, focusing on Islamic Religious Education (IRE) subjects. The study adopts a case study approach to explore how the Qur'anic interpretation method impacts students' understanding of ethical concepts. Data were collected through semi-structured interviews, classroom observations, and document analysis. Thematic analysis was employed to analyze the data, revealing nuanced insights into the relationship between the Qur'anic interpretation method and students' ethical understanding. The findings suggest that the Qur'anic interpretation method significantly contributes to enhancing students' comprehension of ethics, emphasizing the importance of integrating religious texts into educational curricula to promote moral development among students.